A review of neuroimaging studies of race-related prejudice: does amygdala response reflect threat? - Chekroud, Adam M.; Everett, Jim A.; Bridge, Holly; Hewstone, Miles (Frontiers in Human Neuroscience, 2014)
Prejudice is an enduring and pervasive aspect of human cognition. An emergent trend in modern psychology has focused on understanding how cognition is linked to neural function, leading researchers to investigate the neural correlates of prejudice. Research in this area, using racial group memberships, quickly highlighted the amygdala as a neural structure of importance. In this article, we offer a critical review of social neuroscientific studies of the amygdala in race-related prejudice. Rather than the dominant interpretation that amygdala activity reflects a racial or outgroup bias per se, we argue that the observed pattern of sensitivity in this literature is best considered in terms of potential threat. More specifically, we argue that negative culturally-learned associations between black males and potential threat better explain the observed pattern of amygdala activity. Finally, we consider future directions for the field, and offer specific experiments and predictions to directly address unanswered questions.